ANALISIS MATERIAL REQUIREMENT PLANNING DENGAN METODE ECONOMIC ORDER QUANTITY DAN PERIOD ORDER QUANTITY (Studi Kasus : Coffee Shop Bacarito Kopi Padang ) - Abdillah Janaki Daosti; Defri Ahmad (UNIVERSITAS NEGERI PADANG, 2021)
Inventory control and planning is one of the important things to carry out production activities. To get optimal inventory control, it can be done by using lot sizing technique with Eqonomic Order Quantity and Period Order Quantity methods. The purpose of this article is to minimize inventory costs by comparing the Eqonomic Order Quantity and Period Order Quantity-based lot sizing methods based on Material Requirement Planning to obtain minimal inventory costs at the Bacarito Kopi Padang coffee shop. The Bacarito Kopi Padang coffee shop is one of the SME coffee shops that still controls inventory using conventional methods that have not yielded maximum results. This research is an applied research and the data used are data on ordering costs, storage costs, large requests and the company's Total Inventory Cost. The total value of Total Inventory Cost (TIC) which is the minimum optimal is 23,3% for coffee type raw material, 13,5% for full cream milk raw material, 31,5% for syrup type raw material and 49.1% for raw material type sweetened condensed milk by 26,2%.